The Effect of the Development of a Core-Team Youth Thai-Muslim Program toward Violence Prevention among Youths in Southern Thailand - คงสุวรรณ วินีกาญจน์; สุทธรังษี วันดี; นาลีสิน ศรีสุดา (Nursing Journal CMU, 2019)
The purpose of this quasi-experimental research was to examine the effect of a development program for a core-team youth thai-muslim group toward violence prevention. The sample was 480 students who have studied in pattani, yala, narathiwat and songkhla provinces Data was gathered using a violence management skill questionnaire, attitude towards violence questionnaire, and an aggressive behavior questionnaire. Data were analyzed using frequency, mean, standard deviation, and independent t-test. Major findings were as follows: Experimental groups had lower mean score of aggressive than control groups significantly at .05 even though there was no significantly difference on violent management skills and attitude towards violence. However, examining in each province, there was significant differences among violent management skills and attitude towards violence differently among each province. This study suggests that the development of a core-team adolescence thai-muslim program can reduce aggressive behavior and promote more favorable attitudes towards violence, including enhancing violence management skills among thai-muslim adolescents. The difference among each context should be taken into the consideration for the program. Suggestions to extend the application of this program for education in various contexts and to expand knowledge for nursing and other disciplines are being discussed with each of these stakeholder groups.